The reality of the means of technology mechanism and the non mechanism and technology presentations at the basic education level in Palestine - Awad, Mounir Said (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed to reveal the reality of the means of technology mechanism and the non mechanism and technology presentations at the basic education level in Palestine from the perspective of teachers in basic education. To achieve this, the researcher used descriptive and analytical approach, to achieve the objectives of the study, and study sample consisted of (77) teachers in basic education in the northern Gaza Strip in Palestine, and to achieve the objectives of the study, was developed two tools of study, which is about questioners specially designed for the purposes of the study to reveal the reality of the availability and utilization means IT automated and non-automated technology offers in basic education in the northern Gaza Strip, and included questioner on (43) items distributed in three key areas (technology means automatic and non-automatic and technology offers), the study found the following results :  Results of the study indicated that the degree of availability of technology offers received the highest percentage of which (78%), then the technology means non-motorized axis and got a percentage (49%), then a hill axis technology mechanical means and got the lowest percentage (45%) the result at the level of the tool as a whole has got a percentage (51%), the proportion of middle-class availability means technology mechanism and the non mechanism and technology offerings. Results of the study indicated that the degree of use of technology offers received the highest percentage (71.8%), then the technology means non-motorized axis, and got a percentage (49.8%), then a hill axis technology mechanical means, and got the lowest percentage (39.7 %), while the tool as a whole has got a percentage (48.21%), the proportion of middle-class means using technology mechanism and the non mechanism and technology offerings. Study results to the absence of significant differences when Mistoy (0.05≥ α) in degrees availability and use, means technology mechanism and the non mechanism and technology offerings in the primary stage of education from the teachers' point of view, according to the variable of each of (sex, experience, and the school and Qualification) at the level of the whole tool.
Keywords: technology; Automation technology; Non-automated technology; Presentation Technology; basic education stage; North Gaza; Palestine